Optimizing Subsurface Geotechnical Data Integration for Sustainable Building Infrastructure - Nauman Ijaz; Zain Ijaz; Nianqing Zhou; Zia ur Rehman; Hamdoon Ijaz; Aashan Ijaz; Muhammad Hamza (Buildings)
Sustainable building construction encounters challenges stemming from escalating expenses and time delays associated with geotechnical assessments. Developing and optimizing geotechnical soil maps (SMs) using existing data across heterogeneous geotechnical formations offer strategic and dynamic solutions. This strategic approach facilitates economical and prompt site evaluations, and offers preliminary ground models, enhancing efficient and sustainable building foundation design. In this framework, this paper aimed to develop SMs for the first time in the rapidly growing district of Gujrat using the optimal interpolation technique (OIT). The subsurface conditions were evaluated using the standard penetration test (SPT) N-values and soil classification including seismic wave velocity to account for seismic effects. Among the different geostatistical and geospatial models, the inverse distance weighting (IDW) model based on an optimized spatial analyst approach yielded the minimum error and a higher association with the field data for the understudy region. Overall, the optimized IDW technique yielded root mean square error (RMSE), mean absolute error (MAE), and correlation coefficient (CC) ranges between 0.57 and 0.98. Furthermore, analytical depth-dependent models were developed using SPT-N values to assess the bearing capacity, demonstrating the association of R2 > 0.95. Moreover, the study area was divided into three geotechnical zones based on the average SPT-N values. Comprehensive validation of different strata evaluation based on the optimal IDW for the SPT-N and soil type-based SMs revealed that the RMSE and MAE ranged between 0.36–1.65 and 0.30–0.59, while the CC ranged between 0.93 and 0.98 at multiple depths. The allowable bearing capacity (ABC) for spread footings was determined by evaluating the shear, settlement, and seismic factors. The study offers insights into regional variations in geotechnical formations along with shallow foundation design guidelines for practitioners and researchers working with similar soil conditions.